PERSIDANGAN SECARA ELEKTRONIK DI PENGADILAN PAJAK INDONESIA (E - TAX COURT) : KENDALA DAN DAMPAKNYA - Berliana; Zein Sgn, Subhan (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Initially, e-Court was formed from PERMA Number 3 of 2018, over time and in the era of digitalization, the Supreme Court continues to strive to find breakthroughs or innovations in developing a litigation system in the Court, namely by using e-Court in accordance with PERMA Number 1 of 2019 which regulates e-Filling, e-payment, e-summons, and e-litigation. The development and launch of e-Tax Court also reflects the commitment of the Supreme Court of the Republic of Indonesia in integrating information technology (IT) with procedural law, proving that IT innovation Based on this description, this study aims to determine the extent of the effectiveness of e-Tax Court implementation in the Indonesian Tax Court. This type of research is qualitative research which tends to be in the form of analysis in accordance with facts in the field and is complemented by an empirical juridical approach. This study uses primary data sources obtained from interviews with e-Tax Court Information and Technology officers, clerks, tax consultants and tax lawyers, as well as the author making observations on tax clients and tax consultants. Secondary sources used such as books, journals, previous research, articles related to the theme and selected. The results of this study are discussing legal reform in the tax court and measuring the level of effectiveness of the e-Tax Court in the Indonesian Tax Court with an analysis of legal reform and knowing the settlement of litigants in the Indonesian Tax Court with the principle of a simple, fast, and low-cost trial. In reality, the implementation of e-Tax Court in the Indonesian tax court is very efficient and helps a lot in terms of more efficient trials of time and distance, considering that tax courts only exist in a few provincial cities. Of course, there are impacts and things that must be improved from the constraint factors in the implementation of the e-Tax Court from access to server error data uploads, evidence and magic information as well as expert statements who must take oaths, taxpayers or people who still do not master technology, lack of socialization programs to taxpayers. In view of legal reforms and the impact of e-Tax Court settlement of trials, the implementation of e-Tax Court has been achieved optimally, it's just that efforts need to be made to several impacts that hinder the trial such as: Data security, servers, capacity of file, and internet network.